S46 Is pseudomonas infection a necessary precursor to ntm infection in non-cf bronchiectasis?. (15th November 2017) - Elsayed, M; Doherty, E; Marchand, C; Malin, A
Abstract : Background: Non-tuberculous mycobacterial (NTM) infection is more prevalent in those with bronchiectasis than the general population. In addition, Pseudomonas is frequently isolated in more severe bronchiectatic disease. We interrogated our non-CF bronchiectasis database to identify association. Method: A retrospective analysis of 232 patients with non-CF bronchiectasis distinguished those both with and without NTM infection. Analysis included demographic, clinical, microbiologic, lung function and radiological data over a 10 year period. Results: NTM were cultured in 29 patients (12.5%), M gordonae being the most frequent (n=11, 37.9%) followed by M avium-intracellulare (n=9, 31.0%). Pseudomonas infection, current or previous, was identified in 146 (62.9%). Of those with NTM infection, a history of Pseudomonas infection was very strongly associated (96.6%) with only a single case of NTM isolated without Pseudomonas (3.4%; p=0.001) (figure 1 ). Also, concurrent proton pump inhibitor use in the NTM group showed a strong association (55.2% vs. 29.06%; p=0.03). Conclusion: A 10 year analysis of our non-CF bronchiectasis cohort indicates a very strong association between prior Pseudomonas infection and subsequent NTM isolation, with an NTM negative predictive value 98.8% in the absence of Pseudomonas . Whilst association is not causation, we postulate that Pseudomonas may lead to specific mucosal microbiome and structural changes. Moreover, this may be a necessary antecedent prior to observing the very high NTM prevalence rates found in this condition.